Integrated biomass ash smartphone electricity: the utilization of incense ash waste to renewable electricity based mobile application in the village of Nusa Penida, Bali to realize Indonesia on energy objectives 2045 / Yasma Aziza Ul Akrimah ... [et al.] - Ul Akrimah, Yasma Aziza; Zainurrahman, Muhammad; Yuda, Wayan Wira; Ikhsan, Aqshal Nur; 'aisy, Rosyidah Rihhadatul (2020)
Incense is a tool used worship in some religions. The ash of the result of burning incense will be thrown away. Whereas, the composition of the result of the burning incense contains 25%-45% calcium carbonate, less than 10% of potassium, and a variety of heavy metal. Based on Problem new innovation called ELSTATE, which is a mobile app-based tool. This tool can produce electric source from incense ash waste as a substrate with smartphone integrated. The method is Biophotofuel Cell (BPFC), which uses photoanode TiO2 and catode O2-reductor in order to make a decomposition of photoelectrochemical. The result produces electric power with a certaint amount of voltage. This app is hoped be able to control voltage and can be switched on and off automatically. This app will soon be developed in a form of interface so the user can easily use it. This technology is also hoped to minimize the electrical crisis in an area that has lots of incense ash waste but bad at utilizing it. With the voltage of DC 12 V to AC 220 V 500 W which has level of voltage efficiency up to 95%, so that it can answer SDGs Point 7 about Clean Energy.